Evolution and persistence of Arctic and Antarctic stratospheric polar vortex over the 1979 - 2021 period - Lecouffe, Audrey (HAL CCSD, 2021)
This PhD study focuses on the study of the evolution of the stratospheric polar vortices over the last forty years. The intensity and position of the Southern and Northern stratospheric polar vortex edge are evaluated as a function of equivalent latitude over the 1979 - 2021 period on 3 isentropic levels in the lower and middle stratosphere (675 K, 550 K and 475 K) from ECMWF ERA-Interim reanalysis. An analysis of the onset and breakup dates of the polar vortices is included. The solar cycle and to a lower extent the quasi-biennal oscillation, El Niño Southern Oscillation and the Arctic Oscillation modulate the interannual evolution of the strength of the vortex edge and the vortex breakup dates. In the SH, long-term increase of the vortex edge intensity and breakup dates is observed over the 1979 - 1999 period, linked to the increase of the Antarctic ozone hole. After early break-ups between 1981 and 1987, more persistent vortex occured in the NH during the 1990s. For both hemispheres stronger vortex edge and longer vortex duration is observed in solar minimum (minSC) years. For the SH, the vortex edge is stronger and lasts longer for maxSC/wQBO years than for maxSC/eQBO years, and is somewhat stronger during cold ENSO phase (cENSO). For the NH, the stronger vortex edge is more pronounced than in SH during the wQBO phase, and it is stronger during minSC/wQBO years. Ce travail de thèse porte sur l'étude de l’évolution de l'intensité et de la position de la bordure du vortex en fonction de la latitude équivalente sur la période 1979 - 2021 sur 3 niveaux isentropes (675 K, 550 K et 475 K) issus des réanalyses ECMWF ERA-Interim. Une analyse des dates de formation et de rupture des vortex polaires est incluse. Le cycle solaire et dans une moindre mesure, l'oscillation quasi-biennale, l'oscillation australe El Niño et l'oscillation arctique modulent l'évolution interannuelle de l’intensité de la bordure et des dates de rupture du vortex. Dans l’HS, une augmentation à long terme de l'intensité de la bordure du ...